Dejar de fumar desde casa: el "Programa 2001 para dejar de fumar” - Becoña, Elisardo; Míguez, Mª Carmen (Psicooncología, 2006)
The self-help smoking programs have demonstrated to be effective so that many people stop smoking. In the present paper we describe the origin, foundations, characteristic and results of a psychological program to stop smoking through the postal mail, named “Programa 2001 para dejar de fumar” [“Program 2001 to stop smoking”] (Becoña, 1996). This program can be combined with phone advice, write feedback or additional support by email. This treatment is an adaptation in format of self-help of the cognitive-behavioural psychological treatment “Programa para dejar de fumar” [“Program to stop smoking”] (Becoña, 1993) that has shown a good efficacy and cost-effectiveness. The “Program 2001 to stop smoking” was applied in Spain, at national level, from the year 1995. In this years have already participated in it more than 4.500 smokers. Your cost-effectiveness is excellent (until 27% of abstinence at 12 month follow-up) in relation with other clinical treatments, such psychological as pharmacological.